Analisis Perbandingan Waktu Boarding Dengan Aviobridge Dan Tanpa Aviobridge Di Bandar Udara Internasional Supadio Pontianak - Marlan Marlan; Kartika Fajar Nieamah (Pusat Riset dan Inovasi Nasional, 2023)
Air transportation has one of the most influential punctuality factors in the world of aviation, namely On time performance (OTP) which is one of the performance assessment indicators for airline companies. There are several factors that influence the On time performance (OTP) of a flight, one of which is the boarding process, conditions at Supadio Pontianak International Airport seen from the boarding process, parking stand 7 passengers do not use the Aviobridge so passengers have to go downstairs on foot to the apron from the waiting room. to the plane or from the plane to the terminal. Where movement on the apron can cause accidents and take quite a long time. So that it influences the achievement of On time performance (OTP). In the parking stand boarding process, 5 passengers are provided with Aviobridge facilities, where the boarding process is faster than those who do not use Aviobridge/airbridge. The aim of this research is to find out the average time needed for boarding with an Aviobridge, without an Aviobridge and a comparison of the average time using an Aviobridge and without an Aviobridge at Pontianak Supadio International Airport. The method used in this research is descriptive quantitative, the research object is Supadio Pontianak International Airport, the data used is boarding time data for parking stands 5 and 7 during June 2023, the analysis is carried out using statistical tests and comparing the average boarding time at parking stand 5 which uses an Aviobridge and parking stand 7 which does not use an Aviobridge. As a result of this research, it was found that the calculation results of the average boarding time for parking stand 5 using an Aviobridge in one month during June 2023 were 22.56 minutes, the calculation results of the average boarding time for parking stand 7 without an Aviobridge in one month during June 2023 is 39.14 minutes and the difference in average boarding time between parking stand 5 and parking stand 7 is 16.58 minutes.